A Packaged Self‐Powered System with Universal Connectors Based on Hybridized Nanogenerators. Issue 5 (4th December 2015) - Shi, Bojing; Zheng, Qiang; Jiang, Wen; Yan, Ling; Wang, Xinxin; Liu, Hong; Yao, Yan; Li, Zhou; Wang, Zhong Lin
Abstract : A packaged self‐powered system by hybridizing nanogenerators (PSNGS) is demonstrated. The performance of the PSNGS is tested in a biofluid and used for powering an electronic thermometer. Select waterproof universal connectors are designed and fabricated for energy and signal transmission. This PSNGS and the connectors can significantly advance the development of self‐powered implanted medical devices and wearable/portable electronics.